Figurative Language Found In The Song Lyric “Jealously” By Olivia Rodrigo - Maria Yasinta Endang; I Putu Andri Permana (Indonesian Journal Publisher, 2026)
This article discusses the figurative language used in the lyric song Jealously by Olivia Rodrigo. The author assumes that the song’s figurative language is intended to pique the interest of music fans in describing their feelings. The article entitled ‘an analysis of figurative language in the lyric song Jealously by Olivia Rodrigo aims to identify what types and find the meaning of the figurative language in the song. To analyze the data, the main theory used in this article is the figurative language theory proposed by Arp and Perrine (1991), Meanwhile to analyze the meaning the writer proposed the theory by Leech (1981). The data on the song lyric was collected by downloading the song from youtube, listening to and understanding the song lyric, and taking notes classifying the data based on figurative language. As a result of this analysis, the researcher found 5 types of figurative language found in song lyrics. They were simile consisted of 1 (16%) word, overstatement had 1 word (16%), personification 2 words (36%), irony 1 word (16%), and paradox 1 word (16%). The data were analyzed descriptively by using qualitative methods. The data is taken from one edition of the song released in 2021. These lyrics convey a deep feeling of sorrow and regret. The jealousy expressed is not related to doubts about infidelity, but instead highlights the unbearable hurt of witnessing an ex-lover move forward and discover joy with another person.